HUBUNGAN ANTARA KEBIASAAN MAKAN PAGI DAN STATUS GIZI DENGAN PRESTASI BELAJAR PADA ANAK DI SD NEGERI 096132 PARAPAT KECAMATAN GIRSANG SIPANGAN BOLON KABUPATEN SIMALUNGUN TAHUN 2014 - Bethesda Simbolon; Albiner Siagian; Muhammad Arifin Siregar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Breakfast is very beneficial for elementary school children to maintain endurance, so  they can have an activity or study well, helping to focus and easily to understand the lesson, as well as to help provide the nutrients. The purpose of this study is to analyze the correlation between breakfast habbits and nutritional status with academic achievement of elementary school children in SD Negeri 096132 Parapat Kecamatan Girsang Sipangan Bolon Kabupaten Simalungun 2014. This study is a descriptive survey using Cross sectional study design. Data were collected by interviewing students using questionnaire and a 24-hour food recall. Childrend’s learning achievement data obtained from the value of the monthly report cards of childrens. Nutritional status of children was measured by using body mass index for age (BMI/Age). The chi-square test result showed that there is no correlation between breakfast habbits with learning achievement of childrens (p=0,055), there is no correlation between breakfast habbits with nutritional status of childrens (p=0,056). There was a significant correlation between nutritional status of childrens with learning achievement (p=0,012). The correlation of nutritional status and academic achievement is an indicator of how important to have an attention to the nutritional status of children to increase the ability of  brain and body. Based on the results of the study suggested to the parent’s of children to give more attention to their child nutrition covering the quantity, quality and nutritional value which is contained in food material. If children have a good nutrition it will form a good nutritional status and be able to compete in the world of education. And for the school, it have to monitoring the types of food or snacks which is provided in school cafeteria, so that children will receive a good donation of nutrition from food that eat by them. Keyword          : breakfast, nutritional status and learning achievement